Simple Key Distribution For Secure And Energy Efficient Communication In Wireless Sensor Networks - M. Karthik; R. Balakrishna (International Journal of Computational and Experimental Science and Engineering, 2025)
WSNs are used extensively in military and environmental monitoring applications. The appropriate use of limited and insufficient resources is the fundamental problem facing WSNs. Since sensor nodes have limited battery life, efficient use and energy conservation become essential and inevitable problems in prolonging the life of WSNs. Providing security is also crucial because hackers can easily access these networks. WSN security is a crucial component that differs greatly from wired networks’ conventional security measures. However, the key objectives of the safe data aggregation strategy are to reduce network data redundancy, minimize the energy consumption of Sensor Nodes (SN), and precisely maintain information quality. This is largely due to encryption standards, which employ shorter keys and require less RAM to store them. Lightweight encryption has been proposed in recent studies as a solution to the resource restriction problem. In order to increase encryption efficiency, the lightweight encryption technique reduces the security margins utilized by conventional cryptographic approaches. The following privacy and energy dependability concerns need to be effectively addressed in order to meet the WSN targets: secure clustering and routing, key management, and robust encryption procedures. Nevertheless, the majority of earlier studies have focused on addressing a single aspect of WSN safety issues. For maximum effectiveness, a protective mechanism must be put in place. A new Dynamic Step-wise Tiny Encryption Algorithm (DSTE) method for secure and energy-efficient communication in WSNs is proposed in this work.